A rare case of insulinoma presenting as cardiac arrest - Varun Suresh (Wolters Kluwer Medknow Publications, 2019)
Insulinomas are rare neuroendocrine tumours of pancreas arising from the Islets of Langerhans cells with an incidence estimated at 1 to 4 new cases per million persons per year. Patients with insulinomas usually develop neuroglycopenic symptoms presenting as recurrent headache, lethargy, diplopia, and blurred vision, particularly with exercise or fasting. We report a case of young female patient presenting with unwitnessed cardiac arrest later diagnosed as Insulinoma.